Characteristics and outcomes of ventricular tachycardia and premature ventricular contractions ablation in patients with prior mitral valve surgery. (3rd January 2022) - Khalil, Fouad; Toya, Takumi; Madhavan, Malini; Badawy, Mohamed; Ahmad, Ali; Kapa, Suraj; Mulpuru, Siva K.; Siontis, Konstantinos C.; DeSimone, Christopher V.; Deshmukh, Abhishek J.; Cha, Yong‐Mei; Friedman, Paul A.; et al.
Abstract: Background: Data regarding ventricular tachycardia (VT) or premature ventricular complex (PVC) ablation following mitral valve surgery (MVS) is limited. Catheter ablation (CA) can be challenging given perivalvular substrate in the setting of mitral annuloplasty or prosthetic valves. Objective: To investigate the characteristics, safety, and outcomes of radiofrequency CA in patients with prior MVS and ventricular arrhythmias (VA). Methods: We identified consecutive patients with prior MVS who underwent CA for VT or PVC between January 2013 and December 2018. We investigated the mechanism of arrhythmia, ablation approach, peri‐operative complications, and outcomes. Results: In our cohort, 31 patients (77% men, mean age 62.3 ± 10.8 years, left ventricular ejection fraction 39.2 ± 13.9%) with prior MVS underwent CA (16 VT; 15 PVC). Access to the left ventricle was via transseptal approach in 17 patients, and a retrograde aortic approach was used in 13 patients. A combined transseptal and retrograde aortic approach was used in one patient, and a percutaneous epicardial approach was combined with trans‐septal approach in one patient. Heterogenous scar regions were present in 94% of VT patients and scar‐related reentry was the dominant mechanism of VT. Forty‐seven percent of PVC patients had abnormal substrate at the site targeted for ablation. Clinical VA substrates involved the peri‐mitral area in six patients with VT and five patients with PVC ablation. No procedure‐related complications were reported. The overall recurrence‐free rate at 1‐year was 72.2%; 67% in the VT group and 78% in the PVC group. No arrhythmia‐related death was documented on long‐term follow‐up. Conclusion: CA of VAs can be performed safely and effectively in patients with MVS.